The Influence of Teaching Using English Songs on Students' English Pronunciation Skills at Stikes Eka Hope Palangka Raya - Nata, Ipan Dwi (Advances In Social Humanities Research, 2024)
This study aims to determine the effect of teaching using English songs on the English pronunciation ability of students at STIKES EKA HARAP Palangka Raya. In this study, researchers used a pre-experimental design with one pretest and posttest group. The sample in this study was S1 Nursing students in semester 3 consisting of 20 students. Researchers gave a test using English songs. The research instruments are tests (English songs), pronunciation tests and questionnaires to collect the required data. The results of this study show that the null hypothesis is rejected because the Normal distribution table shows that the important value for the right-tail test for z in ? = .05 is z = 1.65. Since -3.92 > 1.65, the researcher rejected H0: ?1 = ?2 and accepted Ha: ?1<?2. Test results are statistically significant at a rate of 5%. Based on this research, it was found that the use of songs in teaching English produces a significant influence on the competence of students' English pronunciation skills and is very beneficial for students to facilitate them in learning English.